Physical fitness preparation of top-level wrestlers - Baic, M. (International Journal of Wrestling Science, 2023)
INTRODUCTION: Today, about 400 elements of technique and combinations in standing and ground position have been registered in classical wrestling and in freestyle wrestling, that number is over 1000. Physical fitness training eparation for top results. A particularly sensitive area in wrestling is how to balance physical fitness preparation and technical-tactical preparation so that wrestlers are fit for technical-tactical requirements, all to achieve top- level sports achievements.